Global Financial Stability Report, March 2002 : Market Developments and Issues. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2002)
This March 2002 issue of the Global Financial Stability Report highlights that financial markets ended the year 2001 on a positive note. Equity markets recovered and rallied noticeably from their lows of late September. In bond markets, yield spreads of corporate and high-yielding bonds, particularly emerging market bonds, narrowed against the U.S. Treasury. At the same time, the U.S. Treasury yield curve steepened, and the U.S. dollar has strengthened. Financial markets thus anticipate, and have priced in, a recovery in economic activity and corporate earnings during 2002.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet